Article 15 : the right to freedom of association and to freedom of peaceful assembly - Daly, Aoife (Commentary on the United Nations Convention on the Rights of the Child., 2016)
In this commentary, Aoife Daly provides analysis of Article 15 of the UN Convention on the Rights of the Child - the right of children to freedom of association and assembly. Relevant international law text and case law are examined, but this commenary goes beyond this to reconceptualise Article 15. The right is applied to themes as varied as association with family and friends, political demonstrations, and the unionisation of working children, with the special position of children to the forefront of the analysis. Possibilities for progressing the right through UN mechanisms, courts and other arenas are considered. In doing so, this book pushes traditional boundaries to and understandings of association and assembly, drawing-out particularly child-specific elements of this crucial right.